The sign T in Iberian and Celtiberian writings (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Every attestation of the sign T in Iberian and in Celtiberian, some of them only recently known, are analyzed in this paper. These data seem to confirm the view of Untermann, who thinks that T is an allograph of n in Western Celtiberian writing. In Eastern Iberian writing it is seemingly a fourth nasal grapheme, different from those known until now (n, m, ḿ). It seems to be an allograph of the sign found at the sign list of Ger. When this fourth sign is found in a text, it takes a place usually held by ḿ, a fact that hints to a near closeness between them.
Keywords: Iberian Writing; Celtibberian Writing; Ger Sign List; Resonants; Nasals